Synergistic effects of interferon‐beta and nivolumab in oral mucosal melanoma. Issue 1 (25th September 2017) - Fusumae, Takayuki; Kamiya, Koji; Chiang, Binluen; Okada, Hirofumi; Nakano, Naomi; Maekawa, Takeo; Komine, Mayumi; Murata, Satoru; Ohtsuki, Mamitaro
Abstract: Mucosal melanoma is a rare aggressive cancer with a very poor prognosis. Clinical and pathological characteristics of mucosal melanoma differ from those of cutaneous melanoma and there are no established management guidelines for mucosal melanoma. Complete surgical excision is one of the most effective treatments for localized lesions, while targeted therapies and immunotherapies, such as monoclonal antibodies that target cytotoxic T‐lymphocyte‐associated molecule‐4, and the programmed death (PD)‐1/PD‐ligand 1 pathway inhibitors, are treatment options for unresectable or metastatic lesions. Here, we describe the case of a patient with oral mucosal melanoma with multiple metastases. In our case, local injection of interferon (IFN)‐β with dacarbazine–nimustine–vincristine therapy provided antitumor effects on an invasive tumor on the upper gingiva. Nivolumab therapy produced complete remission of lymph node and bone metastases. In contrast, the remaining in situ portion of oral mucosal melanoma on the hard palate was refractory to IFN‐β monotherapy and nivolumab therapy. However, after administration of nivolumab, peritumoral injection of IFN‐β showed rapid therapeutic effects. Our case suggested that nivolumab upregulated the antitumor effects of IFN‐β, which induced the recruitment of CD8 + T cells into the tumor microenvironment contributing to the deletion of tumor cells. Combination therapy of IFN‐β and nivolumab may be a potential treatment option for patients with oral mucosal melanoma.